2019
DOI: 10.1371/journal.pone.0217738
|View full text |Cite
|
Sign up to set email alerts
|

Understanding oral health care team performance in primary care: A mixed-method study

Abstract: Objective This study aims to describe the primary care services carried out by Oral Health Teams (OHTs) in Brazil, and to understand the nuances that lead to different levels of OHT performance. Material & methods A mixed-methods study with a sequential explanatory design was developed. In the quantitative phase, secondary data from a national survey (PMAQ-AB) was used to describe the work of 12,403 OHTs. Item response theory (IRT) was applied, to evaluate the psychomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
0
11
1
7
Order By: Relevance
“…Other studies have revealed lacunas in the work process of the teams [ 26 , 35 , 51 , 58 ], but our research identifies alarming data, i.e., the increase in the prevalence of PHC teams with “worse completeness” in Cycle II, representing an increase in the proportion of teams that do not perform any of the work processes indicators surveyed, is considered a serious barrier to potential access to oral health services.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Other studies have revealed lacunas in the work process of the teams [ 26 , 35 , 51 , 58 ], but our research identifies alarming data, i.e., the increase in the prevalence of PHC teams with “worse completeness” in Cycle II, representing an increase in the proportion of teams that do not perform any of the work processes indicators surveyed, is considered a serious barrier to potential access to oral health services.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, precarious conditions and inadequacies related to the structure of oral health facilities may cause limitations and difficulties in the use of these services by the community [ 5 , 50 ]. With these limitations, human resources management is considered an essential factor in the provision of quality health services [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OHT are composed by one dentist and one or two dental assistants. OHT provide community actions and surgical, restorative, preventive procedures at PHC level [ 1 ]. Each PHC unit is evaluated and monitored based on the observation of the facilities, health indicators, and interviews with service users and human resources at PHC.…”
Section: Introductionmentioning
confidence: 99%